1999
DOI: 10.1016/s0014-5793(99)01259-4
|View full text |Cite
|
Sign up to set email alerts
|

Urinary isoprostane excretion is not confounded by the lipid content of the diet

Abstract: This study aims to determine if isoprostanes accurately reflect in vivo lipid peroxidation or whether they are influenced by the lipid content of the diet. Isoprostanes were measured in urine of healthy subjects under different conditions of lipid intake and under conditions of oxidative stress (fasting). We found that isoprostanes were not influenced by the lipid content of the diet: the urinary level remained constant over 24 h as well as over 4 consecutive days when switching from high to low lipid intake. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
2
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 20 publications
5
70
2
1
Order By: Relevance
“…Although it had been stated in the past that the formation of isoprostanes was not affected by the lipid content of the diet (Richelle et al, 1999;Willcox et al, 2003), it was recently shown that the abundant amount of n-3 PUFA in the organism leads to the formation of the family of F 3 -isoprostanes and decreases F 2 -isoprostanes (Gao et al, 2006). However, attempts to measure F 3 -isoprostanes have been so far met with only limited success, especially with noninvasively collected samples such as urine (Adiyaman et al, 1998).…”
Section: Discussionmentioning
confidence: 95%
“…Although it had been stated in the past that the formation of isoprostanes was not affected by the lipid content of the diet (Richelle et al, 1999;Willcox et al, 2003), it was recently shown that the abundant amount of n-3 PUFA in the organism leads to the formation of the family of F 3 -isoprostanes and decreases F 2 -isoprostanes (Gao et al, 2006). However, attempts to measure F 3 -isoprostanes have been so far met with only limited success, especially with noninvasively collected samples such as urine (Adiyaman et al, 1998).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, we have shown that urinary excretion of 8-epi-PGF 2␣ and plasma MDA correlate with other more commonly used adiposity indexes, such as BMI and WHR. Nevertheless, we found some specific relations between body fat measures and these two measures of lipid peroxidation that may result from differences in specificity and sensitivity in assessing lipid peroxidation (29,30). MDA is a general indicator of oxidative stress rather than a specific marker of lipid peroxidation and it is known to vary in response to the diet (23,24).…”
Section: Discussionmentioning
confidence: 97%
“…Oxidative lipid damage, referred to as lipid peroxidation, produces a gradual loss of cell membrane fluidity, reduces membrane potential, and increases permeability to ions like Ca 2+ . Oxidative stress has been proposed to be involved in the pathophysiology of many chronic diseases, including atherosclerosis (Gutteridge and Halliwell, 1990) and diabetes (Richelle et al;, and is known to accelerate ageing processes (De la Fuente and Victor, 2000).…”
Section: Discussionmentioning
confidence: 99%